Pentakosta dalam Ruang Pendidikan Agama Kristen: Semangat Pentakosta dalam Transformasi Pengajaran PAK di Era Society 5.0 - Siregar, Viktor Deni; Rame Irma Ida; Rita Evimalinda (Institut Agama Kristen Negeri Toraja, 2025)
Abstract: This study discusses the transformation of Christian Religious Education in facing the Society 5.0 era by adopting the Pentecostal spirit. In the context of global change and rapid technological developments, religious education is required to innovate in order to remain relevant and able to answer the challenges of the times. The approach used in this study is qualitative descriptive by analyzing literature and studying the transformation of the Pentecostal spirit in Christian religious teaching in the Society 5.0 era. The results of the study show that the integration of technology in Christian Religious Education can increase the effectiveness of learning by creating more interactive and meaningful methods. The Pentecostal spirit, which emphasizes courage, creativity, and togetherness, is an important basis for building the character of students so that they are able to face the digital era without losing spiritual values. Therefore, this transformation is expected to provide a positive contribution to the world of education, especially in forming a generation that has a balance between faith and the use of technology. Keywords: Christian Religious Education; Society 5.0; pentecostal spirit; digital transformation Abstrak: Penelitian ini membahas transformasi Pendidikan Agama Kristen dalam menghadapi era Society 5.0 dengan mengadopsi semangat Pentakosta. Dalam konteks perubahan global dan perkembangan teknologi yang pesat, pendidikan agama dituntut untuk berinovasi agar tetap relevan dan mampu menjawab tantangan zaman. Pendekatan yang digunakan dalam penelitian ini adalah kualitatif deskriptif dengan cara menganalisis literatur serta kajian terhadap transformasi semangat pentakosta dalam pengajaran agama kristen di era 5.0 Society. Hasil penelitian menunjukkan bahwa integrasi teknologi dalam Pendidikan Agama Kristen dapat meningkatkan efektivitas pembelajaran dengan menciptakan metode yang lebih interaktif dan bermakna. Semangat Pentakosta, yang menekankan keberanian, kreativitas, dan kebersamaan, menjadi dasar penting dalam membangun karakter peserta didik agar mampu menghadapi era digital tanpa kehilangan nilai-nilai spiritual. Oleh karena itu, transformasi ini diharapkan dapat memberikan kontribusi positif bagi dunia pendidikan, khususnya dalam membentuk generasi yang memiliki keseimbangan antara iman dan pemanfaatan teknologi. Kata-kata kunci: Pendidikan Agama Kristen; Society 5.0; semangat pentakosta; transformasi digital